A NEW CONCEPTIONS OF INTERNATIONAL CRIMES AGAINST HUMANITY AND POSSIBLE JURISDICTION OF THE INTERNATIONAL CRIMINAL COURT IN ENVIRONMENTAL CRIMES. (CIPEEX, 2022)
THE ARTICLE AIMS TO DEVELOP AN ANALYSIS ON THE INTERNATIONAL CRIMINAL COURT JURISDICTION TO ACT ON ENVIRONMENTAL CRIMES AND CRIMES AGAINST HUMANITY. CONSIDERING THE OBSERVANCE AND PREVALENCE OF FUNDAMENTAL RIGHTS, AS WELL AS THE PRINCIPLE OF SOVEREIGNTY, CONSTITUTIONAL FOUNDATION OF THE BRAZILIAN STATE.
Keywords: Direito; Competência; Ecocídio